Performance of tertiary battery made of Prussian blue analogues. (19th August 2021) - Nagai, Ichiro; Shimaura, Yousuke; Shibata, Takayuki; Moritomo, Yutaka
Abstract: Tertiary battery, which can be charged by heating and/or cooling, is a promising energy harvesting device that performs energy conversion during the thermal cycle between low and high temperatures. Here, we investigated the performance of the Na x Co[Fe(CN)6 ]0.87 (NCF87)/Na x Ni[Fe(CN)6 ]0.94 (NNF94) tertiary battery made of paste-type electrodes between 10 and 50 °C. Its performances, i.e. thermally-induced voltage ( V cell ), discharge capacity ( Q NCF87 ) per unit mass of NCF87, and time constant ( τ ) when connected to an external resistance, are well reproduced by the temperature- and charge-derivatives of the redox potential ( V ) of the constituent cathode (NCF87) and anode (NNF94).